PEMBELAJARAN DARING MENULIS TEKS FABEL PADA SISWA SMP KELAS VII DENGAN MENGGUNAKAN PENDEKATAN KONSTRUKTIVISME BERBASIS KREATIF PEMBELAJARAN - Fauzi, Muhamad (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This study aims to determine student learning outcomes in online learning to write fable texts with a constructivism-based creative approach to learning and what difficulties students experience in writing fable texts; to find out students' responses to online learning to write fable texts with a constructivism-based creative learning approach. The method used is descriptive qualitative method. Data collection techniques in the form of tests and questionnaires. The success of learning is seen from the results of the knowledge and skills test which shows the average value of both of them is 73 and has met the achievement indicators. The difficulty of the knowledge test questions with a score of 4 and 5 regarding the command to determine the structure of the fable text, while the difficulty of the skill question with a score of 93 is found in the linguistic rules, namely conjunctions. The results of the response were very good during the learning process by showing a percentage of 83%. Judging from student learning outcomes and the results of student responses, the methods and media used can motivate students in online learning to write fable texts.